Divided lives : the public and private struggles of three accomplished women - Walsh, Elsa. (New York : Simon & Schuster, 1995)
An intimate look at the lives of three contemporary women--television journalist Meredith Vieira, conductor Rachael Worby, and breast surgeon Dr. Alison Estabrook--portrays their conflicts as they struggle to balance their own needs with the needs of those around them.
Also issued online.
Keywords: Vieira, Meredith; Worby, Rachael; Estabrook, Alison; Women -- United States -- Biography